A Review of Field Trips Research from 1989 to 2024: Bibliometric Analysis Approach - Long, Pham Duc; Nga, Nguyen Thuy; Thuy, Nguyen Thi Ha (VNU Journal of Science: Education Research; Vol 42 No 1, 2026)
Field trip acts as a short-term experiential learning to prepare undergraduates for employment. Prior studies have explored various aspects of field trips. However, a comprehensive picture of field trip research has not yet been captured. This paper reports the application of a bibliometric review to revise the development history of field trip publications and depicts the prospective trends for future academic works. The Scopus database was collected and analysed by the VoS viewer software. The findings showed that the number of yearly publications has risen rapidly over the past 35 years. The three most popular journals in field trip education are the International Journal of Science Education, Journal of Geoscience Education, and Environmental Education Research. The United States, the United Kingdom, and Germany are the most influential contributors, with more than half of the articles for the field trip study. Furthermore, four themes are explored: geoscience education, formal and informal learning, active and experiential learning, and the use of immersive technologies in education. The research makes a theoretical contribution to enrich the literature on experiential learning in general and field trip studies in particular. Future studies can select a trendy theme to develop field trip activities at a specific Vietnamese university.